FAKTOR-FAKTOR YANG MEMPENGARUHI FLUKTUASI HARGA KOPI INDONESIA - Ahmad Ridha; Rinaldi Syahputra; Zulkarnen Mora (Jurnal Samudra Ekonomika, 2022)
This study examines and analyzes the factors that influence the price fluctuations of coffee beans in the domestic market from 2008.1-2021.12. Data analysis used the autoregressive distributed lag (ARDL) model. This model can test the cointegration between variables and short-term and long-term relationships. This study finds a long-term balance between Indonesian coffee prices, world coffee prices, exchange rates, and world cocoa bean prices. Price changes in the world coffee market were transmitted to the domestic coffee producer market positively and significantly. However, the inefficient transmission of corrective adjustments in coffee prices at the Indonesian producer level was documented during the study period. In addition, changes in the price of cocoa beans in the global market also affect the fluctuations in the market price of coffee beans in Indonesia in the long term. The exchange rate consistently affects the price of Indonesian coffee beans, while changes in the volume of Indonesian coffee exports have no significant effect in the long term. In the estimation results of the research model in the short term, all variables significantly affect fluctuations in the price of Indonesian coffee producers at different lag levels